Developments in the non-traditional machining of particle reinforced metal matrix composites - Pramanik, Alokesh (ELSEVIER, 2014)
The non-traditional machining of particulate reinforced metal matrix composites is relatively new. However, researchers seem to pay more attention in this field recently as the traditional machining of particulate reinforced metal matrix composites is very complex. This research investigates different non-traditional machining, such as electro-discharge, laser beam, abrasive water jet, electro-chemical and electro-chemical discharge machining of this composite materials. The machining mechanism, material removal rate/machining speed and surface finish have been analysed for every machining process. This analysis clearly shows that vaporisation, melting, chemical dissolution and mechanical erosion are the main material removal mechanisms during non-traditional machining. The thermal degradation and the presence of reinforcement particles mainly damage the machined surface. The understanding of electro-discharge, laser beam and abrasive water jet machining is more developed than that of electro-chemical and electro-chemical discharge machining for particulate reinforced MMC.